Kappa Free Light Chains, Soluble Interleukin-2 Receptor, and Interleukin-6 Help Explore Patients Presenting With Brain White Matter Hyperintensities - Levraut, Michael; Landes, Cassandre; Mondot, Lydiane; Cohen, Mikael; Bresch, Saskia; Brglez, Vesna; Seitz-Polski, Barbara; Lebrun-Frenay, Christine (Frontiers in Immunology, 2022)
Introduction: Many patients are referred to multiple sclerosis (MS) tertiary centers to manage brain white matter hyperintensities (WHM). Multiple diagnoses can match in such situations, and we lack proper tools to diagnose complex cases. Objective: To prospectively analyze and correlate with the final diagnosis, cerebrospinal fluid (CSF) interleukin (IL)-1β, soluble IL-2 receptor (CD25), IL-6, IL-10, and kappa free light chains (KFLC) concentrations in patients presenting with brain WMH. Methods: All patients over 18 years addressed to our MS tertiary center for the diagnostic workup of brain WMH were included from June 1st, 2020, to June 1st, 2021. Patients were separated into three groups; multiple sclerosis and related disorder (MSARD), other inflammatory neurological disorder (OIND), or non-inflammatory neurological disorder (NIND) groups, according to clinical presentation, MRI characteristics, and biological workup. Results: 176 patients (129 women, mean age 45.8 ± 14.7 yrs) were included. The diagnosis was MSARD (n=88), OIND (n=35), and NIND (n=53). Median CSF KFLC index and KFLC intrathecal fraction (IF) were higher in MSARD than in OIND and NIND groups; p<0.001 for all comparisons. CSF CD25 and IL6 concentrations were higher in the OIND group than in both MSARD and NIND groups; p<0.001 for all comparisons. KFLC index could rule in MSARD when compared to NIND (sensitivity: 0.76; specificity: 0.91) or OIND (sensitivity: 0.73; specificity: 0.76). These results were similar to those with oligoclonal bands (sensitivity: 0.59; specificity: 0.98 compared to NIND, and sensitivity: 0.59; specificity: 0.88 compared to OIND). In contrast, elevated CSF CD25 and IL6 could rule out MSARD when compared to OIND (sensitivity: 0.58 and 0.88, specificity: 0.95 and 0.74, respectively). Discussion: Our results show that, as OCBs, KFLC biomarkers are helpful tools to rule in MSARD, whereas elevated CSF CD25 and IL-6 rule out MSARD. Interestingly, CSF IL6 concentration could help identify neuromyelitis optica spectrum disorder, myelin oligodendrocyte glycoprotein antibodies associated disease, and CNS vasculitis. These results need to be confirmed within more extensive and multicentric studies. Still, they sustain that KFLC, CSF CD25, and CSF IL-6 could be reliable biomarkers in brain WMH diagnosis workup for differentiating MSARD from other brain inflammatory MS-mimickers.